Professionalism of Flight Attendants in The Global Era: The Influence of Communication Skills, Cultural Intelligence, Training, and Professional Ethic - Ayu, Endhi Hermina; Subiyanto, Didik; Hadi, Syamsul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates the effect of flight attendant training on professionalism, mediated by communication skills and professional ethics, and moderated by cultural intelligence. Using a quantitative approach with SEM-AMOS, data were collected from 166 flight attendants and trainees at Jogja Flight. Results reveal that training enhances professionalism directly and indirectly through partial mediation by communication skills and ethics. Cultural intelligence negatively affects professionalism but shows a marginally significant moderating effect. Findings highlight the need for integrated training that incorporates communication, ethics, and cultural intelligence to develop professional cabin crews in the global aviation context.